(untitled) (Heritage, 2023)
The subject of the work is various administration operations that have a factual effect, but do not have a legal character in terms of the legal consequences of legal acts, because they implement general and individual acts into legal life or prepare the conditions for their adoption. Namely, the duties and tasks of administrative bodies, in addition to passing legal acts, also include taking material actions that are undertaken in the process of enforcing rights and affect the rights, obligations or legal interests of the parties, with appropriate legal protection in the event of illegal or inexpedient performance of administrative actions. The significance of the administrative actions taken by the administrative bodies in carrying out their tasks and duties is multifaceted, because they are characterized by the characteristics of authoritativeness and iterativeness, depending on whether elements of coercion or restrictions are applied in their execution. The concept and definition of the administration of the shop is regulated by the Law on General Administrative Procedure ("Official Gazette of the RS", No. No. 18/2016 and 2/2023 - Decision of the US RS. See: Authentic interpretation - 95/2018), which was in 2016, in accordance with the tendency of harmonized legislation with the legal system of the European Union, when administrative actions were introduced as a novelty in administrative-legal procedures. Therefore, this type of legislative activity is aimed at the modernization and introduction of the "good governance" system into the legal system of the Republic of Serbia, with the aim of efficiency and promptness in the implementation of certain material procedures that until then did not have an adequate legal definition.